(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The article analyzes the challenges posed by surrogacy to law and its regulatory capacity. Starting from an overview of the Italian and Portuguese case law that has questioned the relationship between surrogacy and dignity, as well as the consequences of surrogacy on parental status, surrogacy is discussed within the frame of the relationship among dignity, self-determination, and the normative, socio-economic and cultural conditions of freedom of choice over one’s own body.